Strategi Grand Royal Denai Bukittinggi dalam Meningkatkan Kepuasan Tamu Melalui Penyajian Makanan Halal - Mitha Arisoepraba; H. Harfandi (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the strategies of Grand Royal Denai Hotel Bukittinggi in enhancing guest satisfaction through the provision of halal food, considering the growing global halal tourism trend and Indonesia's significant potential as a country with a majority Muslim population. Furthermore, the increasing awareness among Muslim travelers regarding the importance of consuming halal food constitutes an essential background for this research. Employing a qualitative approach with a descriptive method, the study was conducted in October 2024 using data collection techniques including observation, interviews with management and guests, as well as documentation. The data were analyzed using a SWOT approach to identify the hotel’s strengths, weaknesses, opportunities, and threats. The results indicate that Grand Royal Denai possesses strengths such as a commitment to halal standards, a professional kitchen team, a strategic location, and menu variety, while its weaknesses include the absence of MUI halal certification and limited digital promotion. The primary opportunity arises from the increasing halal tourism trend, whereas threats involve intense competition among hotels and changes in modern consumer preferences. By leveraging its strategic location and the potential of the halal tourism market, the hotel is able to increase guest visits and enhance overall satisfaction. Overall, the halal food provision strategy has proven effective in improving guest satisfaction; however, the hotel needs to innovate its menu, expedite halal certification, and strengthen digital-based promotion to maintain competitiveness. In addition, this study contributes to the development of halal tourism and serves as a practical reference for other Sharia-compliant hotels.